Growing things and other stories - Tremblay, Paul (William Morrow, an imprint of HarperCollinsPublishers, 2019)
"A chilling collection of psychological suspense and literary horror from the multiple award-winning author of the national bestseller, The Cabin at the End of the World, and A Head Full of Ghosts"--